2006
DOI: 10.1002/jor.20266
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of anterior cruciate ligament cells in vitro by photo‐immobilized epidermal growth factor

Abstract: The purpose of this study was to explore the early treatment potential of anterior cruciate ligament (ACL) injuries using artificial juxtacrine stimulation by photo-immobilization of a growth factor. A photo-reactive epidermal growth factor complex (EGF-Az) was synthesized by conjugating EGF with N-(4-azidobenzoyloxy) succinimide followed by immobilization onto polystyrene culture plates using UV irradiation. ACL cells from human tissues (1 Â 10 5 cells, 100 ml/ well) were cultured as follows: control, no EGF;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…EGF is a potent mitogen that participates in MSCs and fibroblast proliferation [12], [13], and is also involved in the initial phase of tendon healing. Besides MSCs proliferation, EGF treatment also preserves early progenitors within a MSC population [12], and increases the paracrine activity of stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…EGF is a potent mitogen that participates in MSCs and fibroblast proliferation [12], [13], and is also involved in the initial phase of tendon healing. Besides MSCs proliferation, EGF treatment also preserves early progenitors within a MSC population [12], and increases the paracrine activity of stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…As a first approach, subpopulations of hASCs positive for TNMD, STRO-1, CD29, and SSEA-4 markers were isolated and their tenogenic differentiation capacity assessed for 28 days upon culturing cells with various growth factors [GFs: basic-fibroblast GF (bFGF), transforming GF-β1 (TGF-β1) and platelet-derived GF (PDGF-BB)] that are well known regulators of the development and healing of tendon tissue (James, Kesturu, Balian, & Chhabra, 2008;Molloy, Wang, & Murrell, 2003;Woo, Kwon, Lee, & Park, 2007. ) and described to participate in stem cell tenogenesis (Goncalves et al, 2013;James et al, 2008;Nourissat, Berenbaum, & Duprez, 2015).…”
mentioning
confidence: 99%
“…By comparing with the retention time and peak areas of the standards under the same conditions, GC analysis showed SOWPa was composed of glucose and galactose in a molar ratio of 2.01:1.01. Both proliferation and migration of ACL fibroblasts are essential for repair and regeneration (Woo et al 2007). The results from current studies have demonstrated that PRP, SOWPa (100 mg/kg) or PRP þ SOWPa could significantly promote the proliferation and migration of ACL fibroblasts, especially at 72 h post seeding.…”
Section: Discussionmentioning
confidence: 75%